A combined experimental and theoretical approach to determine X‐ray atomic fundamental quantities of tin. (7th June 2018) - Ménesguen, Y.; Lépy, M.‐C.; Sampaio, J. M.; Marques, J. P.; Parente, F.; Guerra, M.; Indelicato, P.; Santos, J. P.; Hönicke, P.; Beckhoff, B.
Abstract : The knowledge of atomic fundamental parameters, such as the mass attenuation coefficients or fluorescence yields with low uncertainties, is of decisive importance in elemental quantification involving X‐ray fluorescence analysis techniques. For example, several databases giving the mass attenuation coefficients are accessible and frequently used within a large community of users. These compilations are most often in good agreement for photon energies in the hard X‐ray ranges. However, they significantly differ for low photon energies and around the absorption edges of the elements. In the case of the fluorescence yields, some authors made a review of measured values found in the literature. However, reliable measurements are not so many illustrating the inherent difficulties. Mass attenuation coefficients of tin were determined experimentally in the photon energy range from 100 eV to 35 keV by using monochromatized synchrotron radiation at SOLEIL (France). The fluorescence yields of the 3 L ‐subshells of tin were also determined using a reflection geometry setup and the X‐ray fluorescence setup of Physikalisch‐Technische Bundesanstalt. The Coster–Kronig factors for the tin L ‐shells were also experimentally determined. The application of high‐accuracy experimental techniques resulted in low uncertainty mass attenuation coefficients and L ‐subshell fluorescence yields that are directly compared with existing databases and with updated relativistic configuration mixing Dirac–Fock calculations including Quantum electrodynamics (QED) corrections.